2000
DOI: 10.1034/j.1399-5448.2000.010304.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin lispro versus regular insulin in children with type 1 diabetes on twice daily insulin

Abstract: The main advantage of insulin lispro in children on twice daily insulin was found to be its greater convenience, this being achieved without a deterioration in glycaemic control. The higher 3 am blood glucose levels in those on insulin lispro could translate to reduced nocturnal hypoglycaemia in some individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…This is not entirely unexpected, as comparable trials in children and adolescents show similar increases as a result of lispro treatment, and the results of the present study are consistent with these trials. 8,[22][23][24] These findings are suggestive of the importance of factors other than insulin, such as patient attitude and lifestyle, in achieving and maintaining good glycemic control.…”
Section: Discussionmentioning
confidence: 90%
“…This is not entirely unexpected, as comparable trials in children and adolescents show similar increases as a result of lispro treatment, and the results of the present study are consistent with these trials. 8,[22][23][24] These findings are suggestive of the importance of factors other than insulin, such as patient attitude and lifestyle, in achieving and maintaining good glycemic control.…”
Section: Discussionmentioning
confidence: 90%
“…The number of patients in each study ranged from 7 to 1008. Of the 48 crossover studies, 19,20,24,25,30,32,33,35,[37][38][39][42][43][44][45]47,48,51,55,56,58,[62][63][64][65][66][67][69][70][71][72][73][74]78,79,[81][82][83]85,87,89,93,96,[100][101][102]121 most lacked or did not mention a washout period. All studies were of open-label design.…”
Section: Study Characteristics and Methodologic Qualitymentioning
confidence: 99%
“…For rapid-acting insulin analogues, we identified 765 citations, of which we reviewed 26 and selected 5 trials [19][20][21][22][23] for inclusion in our analysis. We thus had a total of 68 randomized controlled trials for the current meta-analysis, including 63 trials from the original health technology assessment 13 ( Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Fairchild et al in a NSW study reported that children using insulin lispro in a twice-daily insulin injection regimen had a significantly higher 3.00 hours BGL than those receiving regular insulin, suggesting a lower risk of nocturnal hypoglycaemia with the newer insulin analogue, consistent with data from overseas. 36 Data from WA showed a decrease in episodes of severe hypoglycaemia from 32.9 to 11.4 per 100 patient years in patients going onto pump therapy after a mean follow-up duration of 1.4 years. 22 Local data are not yet available on rates of hypoglycaemia in patients on insulin glargine or detemir-containing regimens.…”
Section: Hypoglycaemiamentioning
confidence: 97%